(untitled) (Journal of International Studies, 2018)
The author, based on practical experience in the implementation of bilateral cooperation between Mongolia and the Russian Federation in the field of education, reveals the main directions of this cooperation and analyzes its key features. The current regulatory and legal framework for Mongolian-Russian cooperation in the field of education is analyzed separately. The article provides a statistical analysis of the number of students studying in Russian universities, the number of programs, the budget quota allocated for training Mongolian students in Russian universities. And the number of Mongolian students studying various forms of training in Russian educational institutions should increase.